Digital Signal Processing
The book begins with an introduction to Digital Signal Processing and its applications. The treatment of the subject is very much simplified in order to have a thorough understanding of the subject. The salient features include: all the topics are explained with suitable examples and clear figures; more than 10 Matlab programs are given; last two years question papers are included with answers; more than 200 short questions and answers are given; and, more than 100 problems are given as assignment with suitable solved problems.
Keywords: Signal processing -Digital techniques